Peran Elite Adat Pada Pilkada Kabupaten Pinrang 2018 - Suhartono, Eka; Nur, Hasruddin (Phinisi Integration Review, 2021)
The study aims to discover (1) the reasons for the indigenous elite to get involved in the 2018 pre-Pilkada in Pinrang district, (2) the role of the indigenous elite in the 2018 Pilkada process in Pinrang district, (3) the adaptation process for the indigenous elite after the 2018 Pilkada in Pinrang district. This study employed qualitative approach, which described descriptively with data collection techniques used were observation, in-depth interviews, documentation, and literature study. The subject selection technique used was purposive sampling. The subjects of the study were 11 informants. The data validity of the study employed triangulation techniques. Based on the results of the study, several findings are discovered, namely, the role of the indigenous elite in the 2018 Pilkada in Pinrang distirict is not merely limited to the pre-Pilkada but also in the process and after Pilkada is carried out. The reasons for the indigenous elite to get involved in the 2018 pre-election in Pinrang district are to maintain the image, charisma, and position held by the indigenous elite and as a form of proof that the indigenous elite is the manifestation of a leader. The role of the elite in the 2018 Pilkada in Pinrang district is toÂ  become the center for regional mapping which is the basis of support, the indigenous elite which is the generality of winning the area where it is located is an instant strategy for the winning team for regional head candidates to win the Pilkada. Apart from that, another role of the indigenous elite is to become a patron for the masses who take sides and believe that the political choice of the indigenous elite is their political choice. The adaptation process of the indigenous elite after the 2018 Pilkada in Pinrang district is a form of response of indigenous elite after Pilkada where the conditions are winner and losers. This adaptation process is filled with various approaches to get the best position in government and for the losing party will try to approach freedom from political sanctions and still get respect and trust from their masses.